A critical analysis of the economic factors of adoption of renewable energy in different Latin American countries - Freitas, João Victor Araújo de; Zattar, Izabel Cristina (Brazilian Journal of Production Engineering, 2025)
Renewable energy sources, such as solar, wind, biomass and geothermal, are sources that regenerate naturally and, therefore, offer a more sustainable alternative to energy sources from fossil fuels. Therefore, in developed countries, large-scale adoption reflects favorable economic policies. However, in underdeveloped or developing countries, economic barriers persist that hinder the adoption of these energy sources. In this context, this article aims to discuss the main limiting factors found in the literature, from an economic point of view, for the adoption of renewable energy in selected countries in Latin America. To this end, a systematic review of the literature was carried out in the Science Direct, Scopus and Web of Science databases. It was concluded that the main economic limiting factors for the adoption of renewable energy are associated with dependence on fossil fuels, high installation costs, lack of infrastructure, financing difficulties and government economic support. It is also noteworthy that selected countries in Latin America were included in the study, since the literature found for these countries is scarce.